EVALUATING THE EFFECTIVENESS OF ESG INVESTING: A REVIEW OF FINANCIAL PERFORMANCE, REAL-WORLD IMPACT, AND MEASUREMENT CHALLENGES - Otabek Pardabaev (TADQIQOTLAR, 2026)
Abstract Environmental, Social, and Governance (ESG) investing has become a central feature of modern financial markets, yet its effectiveness remains the subject of intense academic debate. This review synthesizes key findings from influential studies across three core dimensions of ESG effectiveness: financial performance, real-world impact, and  measurement  quality.  The  evidence  on  financial  performance  reveals  a  divide between  empirical  studies  reporting  neutral-to-positive  risk-adjusted  returns  and theoretical models suggesting that strong investor demand may lower future expected returns.  Real-world  impact  literature  shows  that  active  ownership  can  influence corporate behavior, whereas ESG fund flows exert limited effects on firms’ cost of capital or environmental outcomes. Finally, research on ESG measurement highlights significant  rating  divergence  and  methodological  inconsistencies,  raising  concerns about the reliability of ESG metrics used for capital allocation. By focusing on the most impactful  contributions,  this  review  clarifies  the  major  points  of  convergence  and contradiction within the ESG literature and provides a concise foundation for future research and policy discussion.